Vše ztratilo dřívější samozřejmost – Existenciální prvky v rané povídkové tvorbě Karla Čapka (Boží muka, Trapné povídky) - Janiec-Nyitrai, Agnieszka (Slavia Centralis, 2020)
The aim of this article is to fnd and characterize possible traces of existential motifs in the early short stories of Karel Čapek (Crossroads, Painful stories) and defne the particular realizations of these motifs. In the context of existentialist literature the author attempts to follow and describe the development of Čapek’s thinking, which is refected in the differences between the two collections of short stories.
Keywords: Karel Čapek; existentialism; short story; Czech literature